2017
DOI: 10.4184/asj.2017.11.5.679
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of C1 Pedicle and Feasibility Evaluation of C1 Pedicle Screw Placement with a Novel Clinically Relevant Radiological Classification in an Indian Population

Abstract: Study DesignA retrospective computed tomography (CT)-based morphometric study of 84 C1pedicles in an Indian population focusing on critical morphometric dimensions vis-a-vis C1 pedicle screw placement.PurposeTo determine the feasibility of C1 pedicle screw placement in an Indian population and propose a novel classification system for the same.Overview of LiteratureAt present, C1 pedicle screws are rarely used, and very few studies have focused on the feasibility of pedicle screw placement in terms of racial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…The current study found C1 pedicle height was 4.77 mm, which was consistent with a study by Christensen et al 15 who reported a C1 pedicle height of 4.80 mm in Western Blacks and White Caucasians. The mean height of the C1 pedicle of the current study was greater than the mean heights of the Tan et al 12 study (4.58 mm), Srivastava et al 16 study (4.48 mm), and the Qian et al 17 study (4.43 mm). This likely occurred due to ethnic differences.…”
Section: Discussioncontrasting
confidence: 81%
“…The current study found C1 pedicle height was 4.77 mm, which was consistent with a study by Christensen et al 15 who reported a C1 pedicle height of 4.80 mm in Western Blacks and White Caucasians. The mean height of the C1 pedicle of the current study was greater than the mean heights of the Tan et al 12 study (4.58 mm), Srivastava et al 16 study (4.48 mm), and the Qian et al 17 study (4.43 mm). This likely occurred due to ethnic differences.…”
Section: Discussioncontrasting
confidence: 81%
“…A The line ab was measured as the C1 pedicle length, and the line cd was measured as the pedicle width affect the placement of pedicle screws [15][16][17]. Some scholars described the morphology of the atlas vertebral artery sulcus, but neither of them classified the vertebral artery sulci and investigated the effect of different types on pedicle screw placement [11,[18][19][20]. Therefore, these previous studies were different from the current study.…”
Section: Discussionmentioning
confidence: 76%
“…The diameter and variation of vertebral artery groove directly affect the placement of pedicle screws [16][17][18]. Some scholars [12,19,20,21]described the morphology of atlas vertebral artery groove, but the classi cation was different. There were also studies to guide the placement of pedicle screws according to the height of atlas pedicle [22][23][24][25]; but few reports on pedicle screw placement guided by vertebral artery groove classi cation.…”
Section: Discussionmentioning
confidence: 99%